Methodologial approaches in teaching English grammar - Zhukova, Tetiana; Жукова, Тетяна Василівна (My University, 2022)
UKR: У статті обґрунтовуються різні методологічні підходи до навчання граматики англійської мови. Також пояснюється важливість вивчення граматики в удосконаленні володіння мовою. ////////////// ENG: Different methodological approaches in teaching English grammar are substantiated in the article. Importance of learning grammar for mastering a language is explaine
Keywords: навчання граматики; методики навчання; дедуктивний підхід; комунікативні ситуації.; індуктивний підхід; функціональна граматика; grammar teaching; teaching methodologies; deductive approach; communicative situations.; inductive approach